Carbamazepine-Induced Pure Red Cell Aplasia - Mansoor, C. A.; Priya, Laksmi (International Journal of Epilepsy, 2018)
Antiepileptic therapy is associated with various hematologic disorders. Pure red cell aplasia (PRCA) is a rare disease that may be congenital or acquired. Severe normocytic anemia, reticulocytopenia, and absence of erythroblasts from an otherwise normal bone marrow should raise the suspicion of PRCA. A 32-year-old unmarried woman was admitted with fatigue for 4 months. She had been on carbamazepine therapy for 4 years (200 mg twice daily) for seizure disorder. On evaluation, she was diagnosed to have PRCA secondary to carbamazepine. We describe a patient with carbamazepine-induced PRCA that improved after discontinuation of the drug.
Keywords: antiepileptic therapy; carbamazepine; pure red cell aplasia